PERBEDAAN HASIL BELAJAR BERDASARKAN MINAT MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 252-268 , Taufik Martha (CIVED, 2013)
The purpose of this descriptive  comparative research was to see the differentiation of students’ score of learning based on students’ interest of Construction Engineering Education “PS-PTB 2009-2010”. The population of this research were 140 students of PS-PTB 2009-2010. The sample were 140 respondens which was use  proportional random sampling technique, was about 140 students. Data used were primary data and secondary data. Primary data was gotten from distributing questioners based on students’ interest. On the other hand, secondary data was students’ scoring in learning gotten from UPT Puskom UNP. The result of data analysis shows that there is no differentiation of students’ scoring in learning based on students’ interest of PS-PTB, civil engineering 2009-2010. It can be seen from T test, taccount (-1,14) > ttable. Key words : Interest, learning result.